Risk management practices in tourism industry – a case study of resort management / Nur Rahifah Amirudin, Anuar Nawawi and Ahmad Saiful Azlin Puteh Salin. - Amirudin, Nur Rahifah; Nawawi, Anuar; Puteh Salin, Ahmad Saiful Azlin (Universiti Teknologi MARA Cawangan Selangor, 2017)
The purpose of this research was to identify the risks that influence the operation of a resort, the impact and the risk management techniques used to reduce those risks. One resort was selected as the case study and document analysis and observation were used as data collection methods. This study found that environmental risk, business risk and human resource risk were the most important risks that could influence the sustainability of the resort’s operations. These risks can be managed through the right combination of risk management techniques. Despite weak monitoring activities, incomplete operating procedures and inferior attitude by the workforce seem to impact the management of the resort, fast and intelligent response may be able to overcome the situation and prevent the worst possible outcomes.